Biochar and its influence on soil physical and hydraulic properties - Duarte, Sara de Jesus (2019)
The biochar is a promissor product for the soil improvement as physical, chemical and hydraulic properties. However, there is a lack of information about the influence of biochar rate, particle size, depth, soil texture and time of interaction on tropical climate. This is one of the first studies that analyse these properties under tropical condition. The objective of this study was analyze the effect of biochar (BC) rate and particle size on soil chemical, physical and hydraulic properties on tropical condition. Was acessed the effect BC rate (6.25, 12.5 and 25 Mg ha-1) in Clay loam and sandy soil under laboratory condition on chemical properties (C, N and C/N ratio), physical properties (bulk density, porosity and pore size distribution) and hydraulic properties (water holding capacity and water available content). In field condition, the effect of the Filter cake (FC) and FC + BC rate (6.25, 12.5 and 25 Mg ha-1) was studied in two depth (0-10 and 10-20 cm) in two times of interaction (9 and 18 months) on soil physical (bulk density, porosity and pore size distribution and aggregate stability) and hydraulic properties (water holding capacity and water available content and hydraulic conductivity). To verify the best BC particle size to be applied on the soil, a third study was developed to test the effect of BC particle size (< 0.15; 0.15-2 and > 2mm) in clay loam and sandy soil and to analyze its effects on soil chemical, physical and hydraulic properties. In the first study (effect of BC rate on laboratory condition) a positive effect of BC rate on water availability, microporosity, and on water retention was found, especially for clay loam soil at high BC application, but this influence did not occur for sandy soil, possibly due to the short time of interaction. In the second study (effect of BC rate and FC on physical, chemical and hydraulic properties) the bulk density slightly decreased, and the porosity increased after nine months of interaction upon FC + BC 25 Mg ha-1. However, after 18 months, the FC + BC amount altered the pore size distribution with an increase of micropores, aggregate stability, available water content and its alteration was dependent on the FC + BC rate. Nevertheless, this effect was not verified in the hydraulic conductivity (Kfs). The time of interaction contributes to increasing the Kfs, and the reduction of Kfs was found with the increase of FC + biochar rate, especially in higher amount FC + BC (25 Mg ha-1) of biochar. In the third work (effect of biochar particle size on chemical and physical and hydraulic properties) total carbon content increased mainly in sandy soil compared to control treatment, the highest carbon amount was obtained in the biochar size 0.15-2 mm in loamy soil and < 0.15 mm in sandy soil, while TN content and C/N ratio increased slightly with reduction of the biochar particle size in both soils. These results demonstrated that biochar particle size is crucial for water retention, water availability, pore size distribution and C sequestration. It is evident that is possible to save irrigation water and improve soil chemical and physical properties by applying biochar.